2017
DOI: 10.1016/j.jtemb.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in early phase type 2 diabetes mellitus—A population-based study. The HUNT study in Norway

Abstract: Differences in trace elements levels between individuals with type 2 diabetes and controls have been reported in several studies in various body fluids and tissues, but results have been inconsistent. In order to examine trace element levels in the early phase of type 2 diabetes, we investigated the association between whole blood levels of 26 trace elements and the prevalence of previously undiagnosed, screening-detected type 2 diabetes. The study was conducted as a case-control study nested within the third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 44 publications
(50 reference statements)
6
70
3
1
Order By: Relevance
“…Concentrations of various trace elements including cadmium, chromium, iron, nickel, silver, caesium, lead, rubidium and zinc were investigated in patients with T2DM. Increased Cr and Zn levels were reported in T2DM patients (39,40). Also, we showed decreased Cr and Zn levels in the cells upon 0.1 mmol/L RSG treatment (Figure 3).…”
Section: Discussionsupporting
confidence: 59%
“…Concentrations of various trace elements including cadmium, chromium, iron, nickel, silver, caesium, lead, rubidium and zinc were investigated in patients with T2DM. Increased Cr and Zn levels were reported in T2DM patients (39,40). Also, we showed decreased Cr and Zn levels in the cells upon 0.1 mmol/L RSG treatment (Figure 3).…”
Section: Discussionsupporting
confidence: 59%
“…Recently, the HUNT3 study investigated the relationship between 25 elements and type 2 diabetes [ 7 , 8 ]. The authors concluded that elements such as bromine, cadmium, chromium, iron, nickel, silver and zinc may have played a significant role in the development of diabetes in newly diagnosed type 2 diabetic patients [ 7 ]. In another study by this team [ 8 ], the prevalence of diabetes was positively correlated with the content of some elements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical studies focusing on population-based groups demonstrated that there are conflicting results associated with zinc deficiency and related symptoms in different populations [ 42 , 43 , 44 ]. Moreover, some studies showed a positive correlation between serum zinc and type 2 diabetes risks in either middle-aged and older Finnish men or the Norwegian population as well as in development of liver fibrosis in the Miami adults [ 45 , 46 , 47 , 48 ]. Additionally, Kunutsor and Laukkanen [ 49 ] performed a population-based cohort study in the same country and, due to their data, they suggested that a higher serum zinc concentration is positively and independently associated with incident hypertension in men.…”
Section: Role Of Zinc In Human Healthmentioning
confidence: 99%